Análisis del rol de los medios de comunicación y su contribución en la solución limítrofe de las zonas administrativamente no delimitadas entre los cantones de Montalvo y Chimbo pertenecientes a las provincias de los Ríos y Bolívar - Llanos Gómez, Angy Gabriela (2016)
The problems of limits in Ecuador have been the subject of studies in innumerable texts, each author has proposed a solution, which he considered correct, however these problems that were accentuated after the country will reach its independence and its territorial map Was changing, with the emergence of new provinces, new cantons and parishes these were accentuated. In the case of the provinces of Los Ríos and Bolívar. Once the latter was territorially separated from the first, border problems began in several sectors, but for the purposes of the research developed we have touched on the conflict of limits between the canton Montalvo and the canton Chimbo, Conflict that from The creation of the Special Commission on the Inner Boundary of the Republic (CELIR) presents a solution, so we want to establish the role that media, especially radio, must play in the problems bordering on administrative areas that are not delimited between The designated cantons. Hence, based on the title that gives reason to the study has been determined that the problem exists and that its solution is in the hands of its authorities, without detracting from the fundamental role of broadcasters, social communicators and / or journalists, who have their headquarters Or work in these stations, are tuned in these territorial spaces, so they are demanded of them verticality, clarity, responsibility, contrasting sources and impartiality at the time of reporting. The work developed has, in its theoretical elaboration, the contents of the degree plan established by the authorities of the UTB, prior to obtaining the Degree of Degree in Social Communication, as a result of which the final report has been prepared Tabulated the x answers obtained from the inhabitants of the sectors in conflict, which after their tabulation, analysis and interpretation allowed us to arrive at the conclusions and elaborate the respective recommendations, based on it arriving at the conceptualization of an alternative and as a product of To offer the proposal with the title of Elaboration of a Project for the construction of a culture of peace, based on Buen Vivir, aimed at social communicators and journalists in the province of Los Ríos and Bolivar.